Price‐based spectrum sharing and rate allocation in the downlink of multihop multicarrier wireless networks. Issue 4 (1st December 2014) - Fathi, Mohammad
Abstract : The author addresses the problem of subcarrier sharing with discrete rate allocation in the downlink of multicell and multihop orthogonal frequency division multiple access networks. The co‐channel interference makes the problem computationally intractable. The author therefore models the problem as a non‐cooperative game among the transmitting nodes with smaller scale problems. Each problem is solved using dual decomposition. Moreover, to mitigate the degradation effect of co‐channel interference in this game, the author additionally proposes a price‐based game. This game charges the nodes for their transmit power on subcarriers. Numerical results demonstrate that price‐based game outperforms the non‐cooperative game as a result of distributed interference avoidance. In addition, both the games with subcarrier sharing achieve higher sum‐rate in comparison with resource allocation schemes with no subcarrier sharing.